NORTHERN INDIGENOUS COMMUNITY-LED DISASTER MANAGEMENT AND SUSTAINABLE ENERGY - Datta, Ranjan, 1977- ([S.l.])
1 online resource
Keywords: This book examines how current energy and water management processes affect Indigenous communities in North America, with a specific focus on Canada. Currently, there is no known Indigenous community-led strategic environmental assessment (ICSEA) tool for developing community-led solutions for pipeline leak management and energy resiliency. To fill this lacuna, this book draws on expertise from Indigenous Elders, Knowledge-keepers, and leaders representing communities who are highly affected by pipeline leaks. These accounts highlight the importance of providing Indigenous communities with technical information and advice, allowing them to practise community-led disaster management, and giving them direct access to lawyers and decision-makers. If implemented into current policy and practice, these tools would succeed in helping rural Indigenous communities make strategic choices for sustainable energy management and utilize their lands, traditional territories, and natural resources to develop a robust, sustainable energy future. Prioritizing Indigenous perspectives on energy management and governance, this book will be of great interest to students, scholars, and practitioners working in the fields of energy policy and justice, environmental sociology, and Indigenous studies.